The Regulation of Peptide Mimotope/Epitope Recognition by Monoclonal Antibodies - Smith, Richard Gary (2002)
Protein-based therapeutics play an increasingly important role in medicine, and the exquisite bio-recognition properties exhibited by antibodies has also led the their use in a number of other fields apart from medicine. The increasing use of these molecules requires more efficient methods of purification. A review of the current purification strategies was conducted. Of all the purification methods studied, peptide epitope/mimotope affinity chromatography proved to be the method of choice - resulting in antibodies exhibiting high specific immunoreactivity. The need to tailor unique affinity ligands for each antibody to be purified by peptide epitope/ mimotope affinity chromatography was identified as the major problem with this technique. A review of the technologies available to regulate the antibody-antigen interaction was conducted. Little was published on the use of phage display for the discovery of peptide ligands for use in peptide mimotope affinity chromatography.